دور الإدارة العليا في شركات المساهمة العامة بقطاع الاتصالات بدولة الإمارات العربية المتحدة في دعم وحدة التدقيق الداخلي: The Role of Senior Management in Public Shareholding Companies in the Telecommunications Sector in the United Arab Emirates in Supporting the Internal Audit Unit - Hussain Khalil Alshemsi ,; Abdulla Mohameed Ahmed Ayedh , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص التدقيق الداخلي أصبح أحد أهم وسائل رقابة المنظمات على المهام وتحقيق الأهداف. حيث أن التدقيق الداخلي نشاط مهم لتحقيق المنظمة لأهدافها والالتزام بالنظم والتشريعات، والحد من حالات الغش والفساد المالي والإداري. لذا يهدف البحث أساسا للتعرف على دور الإدارة العليا في شركات المساهمة العامة بقطاع الاتصالات بدولة الإمارات العربية المتحدة في دعم وحدة التدقيق الداخلي. تكوّن مجتمع الدراسة من 3 شركات مساهمة عامة في دولة الإمارات. ولتحقيق أهداف البحث اعتمد البحث على منهج البحث التحليلي ومنهج البحث المقارن، حيث تتبع هذه الدراسة المنهج النوعي من خلال تحليل المحتوى (content analysis)، وتحليل البيانات الثانوية التي تم الحصول عليها من تقارير حوكمة الأداء، وأهم النتائج التي توصل إليها البحث: يوجد دعم إداري لوحدات التدقيق الداخلي من قبل مجالس إدارات الشركات المساهمة العامة في قطاع الاتصالات في دولة الإمارات العربية المتحدة، والدعم الإداري يشمل الصور الخمسة: التخطيط والتنظيم والتوجيه والقيادة والتحفيز والرقابة، وتوجد استقلالية مناسبة لوحدات التدقيق الداخلي، وتأخذ مجالس الإدارات بملاحظات وحدات التدقيق الداخلي وتطبقها. Abstract Internal audit has become one of the most important means of organizations controlling tasks and achieving objectives. As the internal audit is an important activity for the organization to achieve its goals, adhere to regulations and legislation, and reduce cases of fraud, financial and administrative corruption. Therefore, the research aims mainly to identify the role of senior management in public shareholding companies in the telecommunications sector in the United Arab Emirates in supporting the internal audit unit. The study population consisted of 3 public shareholding companies in the UAE. To achieve the objectives of the research, the research relied on the analytical research method and the comparative research method, and the analysis of secondary data obtained from performance governance reports, and the most important findings of the research: There is administrative support for internal audit units by the boards of directors of public shareholding companies in the telecommunications sector in the United Arab Emirates And administrative support includes the five forms: planning, organizing, directing, leadership, motivating and controlling, and there is appropriate independence for the internal audit units, and the boards of directors take and implement the observations of the internal audit units.